MACRO CONTENT ANALYSIS BETWEEN ECO ENZYME AND GREEN TONIC FERTILIZER ON CHILI PLANT GROWTH - Darusman, Darusman (Biocelebes, 2023)
Organic waste is a serious problem in big cities. Eco Enzyme and Green Tonic fertilizer are used to solve the problem and increase the growth of chili plants. Research comparing the macro content of both is needed. Eco Enzyme analysis activities were carried out at the Soil Laboratory, Faculty of Agriculture, Mulawarman University. The activity of planting chili plants was carried out in one of the researcher's houses. The activities carried out in this study were carried out in two stages, namely the first stage of analysing the content of Eco Enzyme and Green Tonic Fertilizer and the second stage of planting chili plants. Green Tonic Fertilizer has a higher Nitrogen content than Eco Enzyme. However, Eco Enzyme has a higher Potassium content than Green Tonic Fertilizer. Based on the results of the research activities that have been carried out, it can be concluded that; observation of the height of chili plants after the experiment shows that the interaction effect and the main effect of applying eco enzyme has a significant effect on the height of chili plants compared to applying Green Tonic fertilizer and the results also show that many leaves using eco enzyme are better than Green Tonic fertilizer.